Genetic Determinants of Inter-Individual Variability in Statin Therapy - Olejnik, Agnieszka; Zheng, Edward; Możdżan, Maria; Biskup, Laura; Huszcza, Beata; Gronek, Konrad; Kaczmarek, Julia; Grandos, Jakub; Gajewski, Dominik; Głowacka, Zuzanna; Kościołek, Kinga (Quality in Sport, 2026)
Statins, or HMG-CoA reductase inhibitors, represent one of the most extensively researched and frequently prescribed pharmacological agents, primarily utilized to reduce cardiovascular risk through the modulation of serum cholesterol levels. Although their efficacy in reducing global mortality and cardiovascular events is well-established, genetic variability persists among different populations which may predispose patients to dose-related adverse effects and reduced efficancy of statin therapy. This heterogeneity has driven a shift in the scientific landscape toward exploring common genetic polymorphisms within the genes encoding genes involved in pharmacodynamic pathways. This review aims to provide a comprehensive analysis of clinically significant polymorphisms within the pharmacodynamic pathways of statins. Methods: A systematic literature review was conducted in accordance with PRISMA guidelines. Databases including PubMed, Embase, and the Cochrane Library were searched for peer-reviewed publications from 2021 to 2025. Following a rigorous selection process based on Evidence-Based Medicine (EBM) criteria. Conclusions: Despite rapid progress in the field of pharmacogenomics, the role of genetic polymorphisms among genes involved in pharmacodynamic pathways of statin therapy still requires more research in order to establish robust evidence of their role in the overall lipid-lowering efficacy of statins.